The Polish experiment 1980—1989 — revolution or transformation? Antinomies of transition from authoritarianism to democracy - Kantyka, Zbigniew (Studia Politicae Universitatis Silesiensis, 2017)
Abstract: The article is an attempt to assess some of the key aspects of the Polish breakthrough of 1980–1989 in the context of the many years of discussion about the nature and consequences of the events that took place during that period. The main considerations include resolving the still valid dilemma of whether it is justified to define this breakthrough as a revolution. The text contains a presentation and evaluation of the main arguments made for and against such a conclusion. In methodological terms, the discourse involves confronting the characteristic features relating to the genesis, goals, process and results of the Polish experiment of 1980—1989, with the theoretical knowledge on the phenomenon of the revolution based on historical analyses and contemporary experience. In science, the term “experiment” is usually used to describe cognitive processes involving an intentional interference of the researcher in the real world in order to acquire cognitive data. It happens, however, that certain unique phenomena and processes characterised by an objective course of events, which scientists can analyse in similar terms to a conventional induced experiment, enter the scope of this concept. In certain circumstances, a systematic observation of events which have not been induced by the researcher, but are exceptional and important in themselves, can provide the key to discovering the sense, regularities, and mechanisms of the real world. This is significant for social and political studies in particular, in which the space for utilising the classical, natural sciences‑based experiment, is very limited. The Polish political events of 1980—1989 made way for further disintegration of the colonial‑imperial division of the world by initiating the fall of the Eastern Bloc. It turned out to be not just an episode, but an effective initiation of a powerful and extensive process that led to a total change in the global geopolitical system. The fact that it happened in the centre of Europe, rather than in its peripheries, exacerbated the surprise of such a course of events, and of its final result in particular. Key words: democratic transformation, revolution, post‑totalitarian authoritarianism, Solidarity movement, Self‑Governing Republic